2020
DOI: 10.3233/jpd-191784
|View full text |Cite
|
Sign up to set email alerts
|

Is Aquatic Therapy Optimally Prescribed for Parkinson’s Disease? A Systematic Review and Meta-Analysis

Abstract: This review entitled "Is aquatic therapy optimally prescribed for Parkinson's disease? a systematic review and meta-analysis" has not been published previously. All authors declare that they have contributed to this paper, have no conflict of interest and have approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 87 publications
0
34
0
Order By: Relevance
“…Physical therapy with exercises aims to preserve mobility and keep the muscles active to maintain the person's independence and quality of life [6]. Another effect of physical exercise in PD is the increase in the brain neurotrophic factors and neurotransmitters and the decrease in neuronal degeneration in the initial stages of the disease [8]. Multicomponent physical exercise is a modality that, rather than isolated training, targets various aspects of physical function, such as cardiorespiratory fitness, muscle resistance, and balance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapy with exercises aims to preserve mobility and keep the muscles active to maintain the person's independence and quality of life [6]. Another effect of physical exercise in PD is the increase in the brain neurotrophic factors and neurotransmitters and the decrease in neuronal degeneration in the initial stages of the disease [8]. Multicomponent physical exercise is a modality that, rather than isolated training, targets various aspects of physical function, such as cardiorespiratory fitness, muscle resistance, and balance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…39 A 2020 meta-analysis by Carroll and coworkers concluded that overall although outcomes for gait, balance, and mobility were positive for aquatic therapy, they did not appear significantly better than land-based approaches, although studies that delivered at least 3-5 sessions/week did show superior outcomes for aquatic versus land-based programs. 40 Both forms of exercise are often used in a combined approach. Aquatic exercise studies have consistently shown high patient satisfaction and adherence, and several studies have also shown gains in quality of life scores and Short Form-36 (SF-36) and Visual Analog Scale pain scores.…”
Section: Aquatic Therapy Use In Parkinsonismmentioning
confidence: 99%
“…In a 2019 metanalysis of 19 studies assessing land‐based exercise with aquatic exercise, Pinto and coworkers concluded that with high confidence aquatic exercise produced better benefits than land‐based exercise on balance and functional mobility, especially for those Parkinson patients with a high risk of falling, while showing that land and aquatic exercise had similar effects on motor impairments, disease severity, and functional mobility 39 . A 2020 meta‐analysis by Carroll and coworkers concluded that overall although outcomes for gait, balance, and mobility were positive for aquatic therapy, they did not appear significantly better than land‐based approaches, although studies that delivered at least 3‐5 sessions/week did show superior outcomes for aquatic versus land‐based programs 40 . Both forms of exercise are often used in a combined approach.…”
Section: Aquatic Therapy Use In Parkinsonismmentioning
confidence: 99%
“…Aquatic exercise (usually swimming and/or aqua aerobics) is being considered as a potential co-adjuvant form of rehabilitation, especially for people with coronary artery disease presenting with musculoskeletal comorbidities (Cugusi et al, 2019) and peripheral arterial disease (Park et al, 2019). In older populations aquatic exercise appears to offer positive outcomes particularly in regard to gait, balance and mobility (Carroll et al, 2019).…”
Section: Introductionmentioning
confidence: 99%